2019
DOI: 10.1007/s10616-018-0215-7
|View full text |Cite
|
Sign up to set email alerts
|

Protective skin aging effects of cherry blossom extract (Prunus Yedoensis) on oxidative stress and apoptosis in UVB-irradiated HaCaT cells

Abstract: Extracts of the cherry blossom plant have been reported to exert various biological effects on human cells. However, no previous investigations have examined the antioxidant and anti-apoptotic effects of these extracts on ultraviolet B (UVB) radiation-induced skin aging. This study explores the underlying mechanisms of the antioxidant and antiapoptotic effects of cherry blossom extract (CBE) in human keratinocyte (HaCaT) cells. HaCaT cells were treated with CBE at concentrations of 0.5, 1.0, and 2.0% for 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 46 publications
(61 reference statements)
0
7
0
2
Order By: Relevance
“…Excessive ROS levels also exert adverse effects on cells by initiating cell death pathways. In particular, the reduced viability and increased ROS generation in keratinocytes play an important role in the destruction and damage to the skin 31 . Interestingly, our report also showed that the pretreatment of SHM increased the cell viability by reducing the intracellular ROS generation in UVB-exposed human keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive ROS levels also exert adverse effects on cells by initiating cell death pathways. In particular, the reduced viability and increased ROS generation in keratinocytes play an important role in the destruction and damage to the skin 31 . Interestingly, our report also showed that the pretreatment of SHM increased the cell viability by reducing the intracellular ROS generation in UVB-exposed human keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…5A). UVB irradiation-induced ROS generation also leads to a decrease in antioxidant enzyme levels and activates the MAPK signaling pathway, which upregulates MMPs (Nelson et al 2004;Wang et al 2019). Consequently, the increased expression of MMPs promotes wrinkle formation (Kim et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The alterations in UV-induced apoptosis regulation may have an important impact on the induction of skin photoaging and skin cancer. Previous studies have demonstrated that the inhibition of excessive apoptosis and the accelerated elimination of ROS induced by UVB could protect the skin from UVB-induced ageing and carcinogenesis [ 43 ]. Our results showed that the tested compounds effectively attenuated UVB-induced oxidative stress and apoptosis, thereby protecting the skin from UVB-induced damage.…”
Section: Discussionmentioning
confidence: 99%